Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.molcel.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

ELAV and FNE Determine Neuronal Transcript Signatures through EXon-Activated Rescue

Abstract: Highlights d Drosophila ELAV regulates all sites of neuronal alternative polyadenylation in vivo d ELAV directly binds to sites of neuron-specific splicing and 3 0 end processing d ELAV represses inclusion of an fne mini-exon that mediates FNE nuclear localization d In ELAV's absence, FNE rescues neuronal alternative polyadenylation and splicing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(146 citation statements)
references
References 75 publications
11
135
0
Order By: Relevance
“…Fourth, the functional overlap of Elav and Fne involves a regulatory interplay, because Elav represses fne alternative splicing that switches it from a cytoplasmic to a nuclear isoform. The hierarchical role of Elav and Fne in neural mRNA processing was also reported in a contemporary study by the Hilgers group [45].…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Fourth, the functional overlap of Elav and Fne involves a regulatory interplay, because Elav represses fne alternative splicing that switches it from a cytoplasmic to a nuclear isoform. The hierarchical role of Elav and Fne in neural mRNA processing was also reported in a contemporary study by the Hilgers group [45].…”
Section: Introductionsupporting
confidence: 61%
“…A comprehensive summary of de novo motif searches are presented in S6 Fig. We obtained similar, but more exaggerated results, when we directly compared introns flanking excluded exons and included exons for differential motifs (S6 Fig) . Visual inspection of upstream introns of the validated ELAV/Hu splicing targets confirm that introns flanking newly validated exon exclusion targets, such as Medea and Axin, and the recently recognition that Fne is an exquisitely sensitive exon exclusion target of Elav [44,45], tend to have far more matches to Elav consensus motifs in flanking introns than the newly validated exon inclusion targets (Fig 3G). Interestingly, the previously known exclusion target arm was the only validated targed that lacked a preponderence of consensus Elav consensus motifs, although it had other U-rich regions (Fig 3G).…”
Section: Plos Geneticsmentioning
confidence: 60%
See 2 more Smart Citations
“…In summary, we found that the eMIC splicing program is recruited to neural tissues by the Elav/Fne-mediated regulation of Srrm234 3′ end processing and that, within this tissue, it modestly overlaps with splicing networks regulated by other RBPs. Interestingly, we identified several RBPs and transcriptional regulators with alternative isoforms misregulated upon eMIC insufficiency (Table S3), placing the eMIC splicing program within a dense network of neural gene expression regulation, similar to previous results from mammalian model systems 64 .…”
Section: Resultssupporting
confidence: 85%